2007
DOI: 10.1002/j.2055-2335.2007.tb00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Insomnia in Older People

Abstract: Although insomnia is a common problem in older people, there have been few therapeutic advances in the last decade. Benzodiazepines continue to be overused and the newer benzodiazepine-like drugs (e.g. zopiclone) are proving to be no more effective and have their own risk of adverse effects. Nonpharmacological management remains the preferred option, but is poorly taught and infrequently adhered to, especially in hospital and residential care settings. Older people themselves often request drugs. Progress towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 99 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…Clinician awareness of preventing adverse events is seen through prescribing habits and patterns. Thus, our findings may reflect channeling of PRN medications to residents susceptible to daytime napping, particularly those with acute rather than chronic insomnia [35]. This study found no association between benzodiazepine use and day-time drowsiness, whereas previous research indicates benzodiazepine users are at a greater risk of somnolence [10, 28].…”
Section: Discussionmentioning
confidence: 65%
“…Clinician awareness of preventing adverse events is seen through prescribing habits and patterns. Thus, our findings may reflect channeling of PRN medications to residents susceptible to daytime napping, particularly those with acute rather than chronic insomnia [35]. This study found no association between benzodiazepine use and day-time drowsiness, whereas previous research indicates benzodiazepine users are at a greater risk of somnolence [10, 28].…”
Section: Discussionmentioning
confidence: 65%
“…42,43 GABA receptors are present throughout the brain, including the ventral lateral preoptic area that controls sleep. 44 Older adults experience changes in the GABA neurotransmitter system, which results in an increased sensitivity to benzodiazepines and predisposes these patients to ataxia, sedation, and cognitive impairment. 18,45,46 Older patients are more susceptible to the potential adverse effects of benzodiazepines because of altered pharmacokinetics and pharmacodynamics.…”
Section: Results Benzodiazepinesmentioning
confidence: 99%
“…Insomnia is associated with sleeping difficulty, daytime sleepiness and fatigue, which can lead to impaired cognitive function, cardiovascular diseases, falls, depression, decreased immunity and other poor health conditions. Even though insomnia is quite common, its therapeutic interventions are few . Hence non‐pharmacological management such as stimulus control, sleep restriction, sleep hygiene education, cognitive therapy, multi‐component therapy, paradoxical intention and relaxation therapy remains the preferred option .…”
Section: Tackling Disorders Of the Elderly Through Whey Proteinmentioning
confidence: 99%
“…Even though insomnia is quite common, its therapeutic interventions are few. 85 Hence non-pharmacological management such as stimulus control, sleep restriction, sleep hygiene education, cognitive therapy, multi-component therapy, paradoxical intention and relaxation therapy remains the preferred option. 86 Here, nutrition intervention can also play an important role.…”
Section: Insomniamentioning
confidence: 99%